Growth slowdowns, middle-income trap, and demographic profile in South Asia - S. P. Jayasooriya (Asian Development Bank Institute (ADBI), 2017)
The middle-income trap (MIT) is a scenario of rapidly growing economies that experience sudden stops and ultimately lead to stagnation at the middle-income level. Economic growth depends on changes in the demographics of a country. Conversely, the demographic change in economic growth has both positive and negative relationships in the literature. Further, testing a neoclassical model of economic growth is not adequately estimated in the field of demographic and growth slowdowns in South Asia. Therefore, the study uses panel data for understanding the structural change in the demographic changes of South Asian economies. The main approach in middle-income trap literature - the growth slowdowns approach - is used in assessing the MIT fitted into the neoclassical model. The unit root test with a structural break is used for identifying the growth slowdowns. Through this specific approach the current paper is devoted to validating the existence of growth slowdown, hence the middle-income trap. Exploiting Eichengreen, Perkins and Shin (2011, 2013) methodology and adjusting it in order to fit for the South Asian countries, this study identifies numerous slowdown episodes from 1960 to 2014. Thus, a probit model with several indicators is examined to identify which specific factors increase or reduce the likelihood of growth slowdown episodes and consequently drive South Asia into stagnation. The determinants of growth slowdown are: significant negative factors, GDP per capita, lagged growth, trade openness, investment share, demographic profile, and FDI. Further, the study revealed that the demographic transition factors are: fertility rate, dependency ratio, young dependency, labor force, demographic profile, and population density.
Keywords: E13; F43; J11; O11; O47; 330; growth slowdown; MIT; demographics; South Asia